Post-endodontic restorative treatments and their mechanical behavior: A narrative review - Guilherme Schmitt de Andrade; Guilherme de Siqueira Ferreira Anzaloni Saavedra; Marina Gullo Augusto; Génesis Alfonzo Leon; Hellen Cristina Budel Brandão; João Paulo Mendes Tribst; Amanda Maria de Oliveira Dal Piva (Elsevier, 2023)
Dental treatment after endodontic therapy is quite challenging in clinical practice. While multiple post-and-core systems emerged and disappeared in the dental field, the historical process was laborious and still requires several up to date scientific evidence. Furthermore, once considered the gold standard, rigid metallic post-and-cores might be considered a limited option. Moreover, the development of glass-fiber posts and the biomechanical principles for root preparation bring multiple advantages, but also raise concerns over guidelines and indications. This review examined the classic literature so that clinicians may understand the concepts behind post endodontic restorative treatments and the doubts that still remain in the daily practice before performing this restorative modality.